2017
DOI: 10.1111/wrr.12513
|View full text |Cite
|
Sign up to set email alerts
|

Non‐animal models of wound healing in cutaneous repair: In silico, in vitro, ex vivo, and in vivo models of wounds and scars in human skin

Abstract: Tissue repair models are essential to explore the pathogenesis of wound healing and scar formation, identify new drug targets/biomarkers and to test new therapeutics. However, no animal model is an exact replicate of the clinical situation in man as in addition to differences in the healing of animal skin; the response to novel therapeutics can be variable when compared to human skin. The aim of this review is to evaluate currently available non-animal wound repair models in human skin, including: in silico, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 119 publications
(296 reference statements)
0
56
0
Order By: Relevance
“…One way to predict the toxicity and pharmacokinetics of substances is through in silico tests, which assess the toxicity of theoretical compounds and aid in the choice of potentially promising molecules [ 11 , 12 , 36 ]. In silico tests revealed that isopropyl caffeate has no theoretical toxicity ( Table 3 ) and has probable activity against several diseases which are directly linked to oxidation ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to predict the toxicity and pharmacokinetics of substances is through in silico tests, which assess the toxicity of theoretical compounds and aid in the choice of potentially promising molecules [ 11 , 12 , 36 ]. In silico tests revealed that isopropyl caffeate has no theoretical toxicity ( Table 3 ) and has probable activity against several diseases which are directly linked to oxidation ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that no chemical is free of toxicity; the study of toxic effects is as necessary as knowledge concerning side effects, interactions, contraindications, and mutagenicity [ 10 12 ]. Substance toxicity is often related to the formation of free radicals, which cause oxidative stress and are responsible for a large number of diseases [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo models mimic human wound healing more efficiently. The widely utilized murine excisional wound model still has some disadvantages because it does not completely model human wound healing due to its inability to prevent skin contracture in rodents (Ud‐Din & Bayat, ). Therefore, we added a silicone splint to prevent unpredicted contracture and covered the wound with Tegaderm (H. Li, Cao, Huang, & Man, ) to maintain proper hydrophilicity (Persin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Animal models have been widely used due to its advantages of comprehensive and systemic experiments [ 15 , 16 ], while they require specialized instruments and workforces to conduct wound healing study with well-controlled experimental environments [ 17 ]. In vitro wound healing models with a simple design, repeatability and low cost have been proposed to resolve these issues [ 18 , 19 ]. For in vitro wound formation methods, mechanical, electrical and optical wound formation have been studied to reproduce various types of wounds, e .…”
Section: Introductionmentioning
confidence: 99%